ULTRASTRUCTURE AND HISTOCHEMISTRY OF VITELLOCYTES ENSURING THE DEVELOPMENT OF OPISTORCHIS FELINEUS EGGS - LYUBOV V. Nacheva; VALERIY M. Grebenschikov (Фундаментальная и клиническая медицина, 2018)
Aim. To study histochemistry and ultrastructure of vitellocytes providing the development of Opisthorchis felineus eggs. Materials and Methods. Opisthorchis felineus eggs were collected from cats with opisthorchiasis. Tissue were examined utilizing toluidine blue and bromphenol blue for nuclei staining, and Coomassie brilliant blue G-250 for protein staining. We further conducted ferric ferricyanide test (Chevremont and Frederic) to identify sulfur-containing amino acids, Feulgen staining to detect DNA, periodic acid-Schiff staining for polysaccharides and mucosubstances, and Sudan Black B for lipids. Electron microscopic examination was carried out after ultrathin sectioning with the following staining with uranyl acetate and counterstaining with lead citrate. Results. Ultrastructure of Opisthorchis felineus vitellocytes was defined by the stage of vitellogenesis. Vitellocytes were positively stained for proteins, SS- and SH-containing amino acids, and also contained small amount of glycogen and lipids. These substances were involved in the formation of vitelline granules aggregating in clusters within the endoplasmic reticulum and representing precursors of vitelline membrane. Conclusion. At sequential stages of their development, vitellocytes produce protein- and lipid-rich granules that ultimately consitute vitelline membrane of Opisthorchis felineus eggs.